Usulan Pembaharuan jadwal Kegiatan Preventive Maintenance pada Mesin Curing PCR PT.XYZ Menggunakan Metoda Distribusi Weibull - Herman Budi Harja; Nunu Ahmad Nugraha (Jurnal Teknologi dan Rekayasa Manufaktur, 2019)
The frequent occurrence of unplanned maintenance of curing machine on PT XYZ car tire production line is an indication of ineffectiveness implementation of the preventive maintenance. Unplanned downtime caused increasing of lost production time and failure products during setup, and also high cost maintenance. The company must improve the effectiveness and efficiency of the maintenance system performance through updating the maintenance schedule for obtaining high availability of the machine. The purpose of this study is to identify the components which cause the failure of the curing machine and give the recommendation of the appropriate maintenance interval. Weibull distribution method is used to get the index value of fit time to failure of machine components, analyze the component failure rate, calculate the mean time between failure (MTBF) as the expected lifetime of the component. The obtained result showed that there were two critical components with an indication of the increasing failure rate, as during wear-out (β value> 1), which are namely cylinder press and EPV with an MTBF value of 89 days for cylinder presses and 231 days for EPV. The results of this study propose for updating the curing machine PM schedule. the adding pressure valve and EPV on PM activities and using the its expected lifetime as its PM interval should be considering. it will minimize unplanned downtime